LEARNING STYLES AND STRATEGY-BASED INSTRUCTION - Iroda Mirzaeva (Galaxy International Interdisciplinary Research Journal, 2022)
Learners tend to differ from one another in regard with their age, temperament, character and learning behaviors. Once the teacher intends to achieve a successful outcome, he or she should pay particular attention to specific tasks which help students learn more easily. The tasks usually are selected based on students’ learning styles.